2002
DOI: 10.1038/modpathol.3880602
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr Virus in Rapidly Growing Fibroadenomas of the Breast in Immunosuppressed Hosts

Abstract: Fibroadenomas are the most common benign tumors of the female breast and are associated with a slight increase in the risk of subsequent breast cancer. Multiple fibroadenomas have been described in patients after renal transplantation and are thought to be secondary to drug-related growth stimulation. Epstein-Barr virus (EBV) has been detected in many neoplasms, including breast cancer. We set out to investigate whether EBV plays a role in the development of rapidly growing fibroadenomas in immunocompromised p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
(19 reference statements)
0
24
1
2
Order By: Relevance
“…The herpesvirus EBV, a causative agent for infectious mononucleosis, has been associated with various malignancies with frequencies that vary from 100% (in poorly differentiated NPC) to a few percent only (in adenocarcinomas) (IARC, 1997), or, as recently discussed, up to 45% (nine out of 20) in fibroadenomas from HIV-positive individuals (Kleer et al, 2002). In some studies, EBV has been identified as a component of breast cancers (Labrecque et al, 1995;Luqmani and Shousha, 1995;Bonnet et al, 1999;Fina et al, 2001;Grinstein et al, 2002;Kleer et al, 2002) in up to 50% of cases examined (Bonnet et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The herpesvirus EBV, a causative agent for infectious mononucleosis, has been associated with various malignancies with frequencies that vary from 100% (in poorly differentiated NPC) to a few percent only (in adenocarcinomas) (IARC, 1997), or, as recently discussed, up to 45% (nine out of 20) in fibroadenomas from HIV-positive individuals (Kleer et al, 2002). In some studies, EBV has been identified as a component of breast cancers (Labrecque et al, 1995;Luqmani and Shousha, 1995;Bonnet et al, 1999;Fina et al, 2001;Grinstein et al, 2002;Kleer et al, 2002) in up to 50% of cases examined (Bonnet et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, EBV has been identified as a component of breast cancers (Labrecque et al, 1995;Luqmani and Shousha, 1995;Bonnet et al, 1999;Fina et al, 2001;Grinstein et al, 2002;Kleer et al, 2002) in up to 50% of cases examined (Bonnet et al, 1999). Interestingly, whereas association of EBV with about 10% of human gastric carcinomas (Shibata and Weiss, 1992;Rowlands et al, 1993;Galetsky et al, 1997;Takano et al, 1999;Yoshiyama et al, 1997;Zur Hausen et al, 2000) is accepted as real and meaningful, the association of this virus with human breast cancer Figure 2 Analysis of expression of EBV RNA in viral DNA-positive breast cancer biopsies (BCs 1, 4, 10 -13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct association has been noted between oral contraceptive use before age 20 and the risk of fibroadenoma [103]. The Epstein-Barr virus might play a causative role in the development of this tumor in immunosuppressed patients [104].…”
Section: Neoplasms Fibroadenomamentioning
confidence: 99%
“…Breast cancer has epidemiological resemblances to young-adult Hodgkin lymphoma [93][94][95], though indication for breast cancer involves timing of initial EBV infection rather than viral oncogenesis [93]. EBV was found in benign breast tumors in immunosuppressed patients [96], and in vitro, breast epithelial cells were infected by direct contact with EBV-bearing lymphoblastoid cell lines [97]. Moreover, the identification of EBV genes or gene products within breast tumors' tissues represents strong evidence for an EBV-breast cancer association [98].…”
mentioning
confidence: 99%